MEC: Mobile for English Course Apps - Ahdon, Mohd Fadli; Mat Yusoff, Ainul Mardhiyah; Abdul Rahman, Lailatul Aimi (Multidisciplinary Applied Research and Innovation, 2021)
Mobile learning which takes place without boundaries and time limitations has led to heutagogy based learning and the Industry Revolution 4.0 covering various areas of learning including English language learning. Hence a mobile learning application called MEC Apps (Mobile for English Course Apps) has been developed as one of the Arau Community College English module learning alternatives which include notes, exercises, references and gamification in an interactive and interesting way. This is due to a pilot study conducted which found that 68.9% of respondents consisting of students at Arau Community College had problems to get additional reading to learn English because of the difficulty in obtaining the necessary reading resources and references. The MEC application was developed as a facility for students especially the younger generation known as digital natives to learn English by far and allows to test comprehension through reinforcement exercises provided. A study was conducted to see the potential use of MEC application by using the Kurt Lewin model in looking at the effect of the use of MEC application on students' attitudes, motivation and self-efficacy. Pre and post-tests were conducted on the study respondents to compare the total marks that had been obtained by the respondents before and after the MEC application was used. The findings showed an increase in scores of 45% from 40% in the pre-test to 85% in the post-test. In addition, a Likert scale testing instrument containing 4 constructs of the Instructional Materials Motivation Survey(IMMS) adopted from Noraini (2008) measurement test was used to test respondents’ feedback while using the MEC application. The results of the study found that mobile learning applied in MEC can be one of the alternatives to the effort in learning English Courses in Arau Community College towards the Industrial Revolution 4.0.